Genetic analyses of essential genes in cytological region 61D1-2 to 61F1-2 of Drosophila melanogaster. - Saito, M.; Awasaki, T.; Hama, C. (Molecular Genetics and Genomics, 2002)
We performed a systematic mutagenesis screen for lethals in the genomic region 61D1-2 to 61F1-2 on chromosomal arm 3L of Drosophila melanogaster. Our genetic analyses revealed that this region contains eight essential complementation groups including trio, Glut1 and extra macrochaetae (emc). For the trio locus, 22 mutant alleles were identified, and all of the alleles analyzed resulted in defects in the central nervous system of embryos, indicating that trio functions in the control of axon extension or guidance. Western analysis showed that at least three proteins are derived from trio and also suggested that a polypeptide of over 200 kDa plays a crucial role in embryonic or larval development. In addition, a newly identified emc allele was associated with several defects in embryonic morphogenesis, including abnormalities in head involution, gut formation and dorsal closure, thus revealing multiple roles for emc in embryonic development. We also performed preliminary phenotypic analyses on stocks bearing mutations belonging to the other lethal complementation groups. These genes function in essential biological events, but the mutations do not result in gross morphological changes during embryonic stages. The present study extends our knowledge of the Drosophila gene set, by identifying most of the essential genes in the chromosomal region 61D1-2 to 61F1-2.